Multiplex polymerase chain reaction test for the diagnosis of acute viral hepatitis A - Heo, Nae-Yun (The Korean Association for the Study of the Liver, 2012)
BACKGROUND/AIMS: The early diagnosis of acute hepatitis A (AHA) is hindered because serum IgM against hepatitis A virus (HAV) can yield false-negative results during the window period. This study evaluated the diagnostic accuracy of a polymerase chain reaction (PCR) kit for HAV RNA for the diagnosis of AHA. METHODS: Samples were collected from 136 patients with acute severe hepatitis at their admission to Asan Medical Center between June 2010 and July 2010. Samples were analyzed for serum IgM anti-HAV using an immunoassay test and for qualitative HAV RNA using the Magicplex HepaTrio PCR test kit. The diagnostic accuracies of these methods were tested on the basis of clinical and laboratory diagnoses of AHA. RESULTS: The concordance rate and kappa value between IgM anti-HAV and HAV RNA PCR were 88.2% and 0.707, respectively. For the diagnosis of AHA, the sensitivity and specificity of IgM anti-HAV were 90.7% and 100%, respectively, when an "equivocal" result was regarded as positive; and 79.1% and 100%, respectively, when an "equivocal" result was regarded as negative. The sensitivity and specificity of HAV RNA PCR were 81.4% and 100%, respectively. All four patients with negative IgM anti-HAV and positive HAV RNA PCR results and all four patients with equivocal IgM anti-HAV RNA and positive HAV RNA PCR results were eventually diagnosed with AHA. CONCLUSIONS: The qualitative HAV RNA PCR test has an equivalent diagnostic accuracy for AHA compared to IgM anti-HAV and may be more sensitive during the window period.